2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6609717
|View full text |Cite
|
Sign up to set email alerts
|

Somnography using unobtrusive motion sensors and Android-based mobile phones

Abstract: Abstract-Sleep plays a fundamental role in the life of every human. The prevalence of sleep disorders has increased significantly, now affecting up to 50 % of the general population. Sleep is usually analyzed by extracting a hypnogram containing sleep stages. The gold standard method polysomnography (PSG) requires subjects to stay overnight in a sleep laboratory and to wear a series of obtrusive devices. This work presents an easy to use method to perform somnography at home using unobtrusive motion sensors.Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Interestingly, investigators were recently able to demonstrate that placing wireless external sensors placed on a bed and integrating them into a mobile phone's platform is almost 80% accurate in distinguishing wakefulness, nonrapid eye movement and REM sleep in a home setting. 16 The use of such additional unobtrusive sensors, making no contact with the subject's body and therefore causing no discomfort, represents a potential means to improve the accuracy of such apps.…”
Section: (20%)mentioning
confidence: 99%
“…Interestingly, investigators were recently able to demonstrate that placing wireless external sensors placed on a bed and integrating them into a mobile phone's platform is almost 80% accurate in distinguishing wakefulness, nonrapid eye movement and REM sleep in a home setting. 16 The use of such additional unobtrusive sensors, making no contact with the subject's body and therefore causing no discomfort, represents a potential means to improve the accuracy of such apps.…”
Section: (20%)mentioning
confidence: 99%
“…Some of these apps can also track body movement during sleep by using the nearly-universal accelerometers included in smartphones, which are affixed to patients with thoracoabdominal bands. 3,28 Prior studies 29-31 revealed that smartphones may be used to perform pre-screening exams with comparable quality to that of traditional polysomnography. To perform polysomnography, smartphones require the implementation of additional hardware, such as a pulse oximeter, accelerometer, and external microphone.…”
Section: Discussionmentioning
confidence: 99%
“…Serious doubts arise about the effectiveness of these apps that can register only snoring but not other simultaneous parameters, such as oxygen saturation or thoracic-abdominal movement. 30,31…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these devices have demonstrated similar validation performance to consumer wearables regarding accuracy to PSG. Regarding general weaknesses, these devices tend to be less accurate for individuals who share a bed with a partner or a pet (80). These types of devices detect movement within a particular space, and thus register partner and pet movements.…”
Section: Comparisons To Wearable Actigraphy Devicesmentioning
confidence: 99%